Use of wastes from the peanut industry in the manufacture of building materials - Quaranta, Nancy Esther (2018)
Most of the national peanut production, estimated at 900,000 tons per year, is processed in several cities in the central area of Argentina. The third part of this amount corresponds to the shells, which are separated in the peanut selection and processing plants. In this work, the possibility of using peanut shells as raw material for the manufacture of ceramic materials for the civil construction industry is studied. There are precedents on the use of biomass residues in different building blocks, mainly with the aim of generating lightweight ceramics. With this objective, ceramic pieces were obtained from green bodies manufactured with mixtures of commercial clay and different percentages of ground and dry residue. After a drying period, the samples were heat treated following curves similar to those used in the ceramic industry. The raw material used, clay and peanut shells, were characterized with different techniques, such as XRD, SEM and DTA-TGA. The DTA-TGA analysis shows that the organic material added is burned in a wide temperature range, between 300 °C and 550 °C. Thus, the sintering process of the bricks is performed without cracking or shattering. This test also shows that after the heat treatment, the waste material eventually incorporated into bricks (ashes) is less than 3%. The obtained products have good physical and mechanical properties, with acceptable values of porosity, modulus of rupture, permanent volumetric variation and weight loss on ignition.